Road Quality in Indonesia: Is it Linked to Special Allocation Funds and Political Competition? - Putri Natalia Saragih; Khoirunurrofik Khoirunurrofik (Signifikan: Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the relationship between decentralization, viewed from a fiscal and political perspective, and the quality of road infrastructure in Indonesian regions. This study uses panel data of 32 provinces in Indonesia in the 2011–2018 and applied pooled ordinary least square (OLS) estimation with individual fixedeffects to capture time-variable estimation. The results show that special allocation funds (DAK) did not significantly improve the quality of damaged roads, although the correlation was negative. The apparent improvement in the damaged-road ratio is presumed to be because the government is currently more focused on the physical construction of roads than on maintenance, so the level/quality of road maintenance is still not optimal. The political competition was found to be negatively related to the improvement of the damaged-road ratio, indicating that political competition improved the quality of budget execution in road infrastructure provision.How to Cite:Saragih, P. N., & Khoirunurrofik , K. (2022). Road Quality in Indonesia: Is It Linked to Special Allocation Funds and Political Competition? Signifikan: Jurnal Ilmu Ekonomi, 11(1), 57-72. https://doi.org/10.15408/sjie.v11i1.21090.